Living with the law : gender and community among the Jews of medieval Egypt - Zinger, Oded (Philadelphia, Pennsylvania : University of Pennsylvania Press, 2023)
"Living with the Law explores the marital disputes of Jews in medieval Islamic Egypt (1000-1250). Examining the rich documents of the Cairo Geniza, a unique repository of discarded paper discovered in Cairo synagogue, the book recovers the life stories of Jewish women and men working through their marital problems at home, with their families, in the street of old Cairo and in Jewish and Muslim courts. Despite a voluminous literature on Jewish Law, the everyday practice of Jewish courts has only recently begun to be investigated systematically. The experiences of those in legal, social and cultural disadvantage allow us to go beyond the image propagated by legal institutions and offer a view "from below" of Jewish communal life and Jewish law as it was lived"--
Jewish marriage 101: In lieu of a glossary -- Introduction -- The legal arena: A social interpretation -- Gender and status in geniza courts -- Compromising women: Gender and property in divorce and married life -- The ties that bind: Kinship support and communal participation -- Conclusion.
Includes bibliographical references and indexes.
Print version record.
JSTOR
Keywords: Jews -- Egypt -- History -- To 1500.; Jewish women -- Egypt -- Social conditions -- History -- To 1500.; Jewish marriage customs and rites -- Egypt -- History -- To 1500.; Jewish courts -- Egypt -- History -- To 1500.; Courts -- Egypt -- History -- To 1500.; Marriage (Jewish law); Marriage law -- Egypt; Cairo Genizah; Juifs -- Égypte -- Histoire -- Jusqu'à 1500.; Juives -- Égypte -- Conditions sociales -- Jusqu'à 1500.; Mariage -- Rites et cérémonies juifs -- Égypte -- Histoire -- Jusqu'à 1500.; Tribunaux juifs -- Égypte -- Histoire -- Jusqu'à 1500; Tribunaux -- Égypte -- Histoire -- Jusqu'à 1500.; Mariage -- Droit juif; Mariage -- Droit -- Égypte.; Génizah du Caire; RELIGION / Judaism / History; Cairo Genizah; Courts; Jewish courts; Jewish marriage customs and rites; Jewish women -- Social conditions; Jews; Marriage (Jewish law); Marriage law; Egypt; To 1500; History